Autoantibodies against C5aR1, C3aR1, CXCR3, and CXCR4 are decreased in primary Sjogren's syndrome. (March 2021) - Yue, Xiaoyang; Deng, Fengyuan; Chen, Juan; Yin, Junping; Zheng, Junfeng; Chen, Yan; Huang, Qiaoniang; Gao, Xing; Liu, Zuguo; Luo, Jiao; Müller, Antje; Heidecke, Harald; et al.
Highlights: Autoantibodies to C5aR1, C3aR1, CXCR3 and CXCR4 are decresed in pSS and RA. Autoantibodies to CXCR3 and CXCR4 correlate with circulating lymphocytes in pSS. Correlation signature of anti-GPCR antibodies is associateded to lung invovlement in pSS. Abstract: Background: Networks formed of numerous autoantibodies (aabs) directed against G-protein coupled receptors (GPCR) have been suggested to play important role in autoimmune disorders. In present study, we aimed to evaluate the association between anti-GPCR antibodies and primary Sjogren's syndrome (pSS) to determine the potential pathogenic factors. Methods: By applying a cell membrane-based ELISA technique, which is capable of detecting aabs against conformational epitopes within GPCR, serum levels of fourteen GPCR were determined in well-characterized patients with pSS (n = 52) and gender-matched healthy controls (n = 54). Comparisons between groups were analyzed by two-tailed Mann-Whitney U test, Bonferroni correction was applied for multiple comparisons. Spearman`s rank correlation coefficients were calculated between variables and visualized by heat map. Results: Compared to healthy subjects, sera of patients with pSS showed significantly higher binding to β2AR and ETAR, but lower binding to C5aR1, C3aR1, CXCR3, and CXCR4. Autoantibodies against C5aR1, C3aR1, CXCR3, and CXCR4 were also decreased in patients with rheumatoid arthritis. In pSS patients, levels of anti-CXCR3 and anti-CXCR4 antibodies were negatively correlated with circulating lymphocyte counts. Furthermore, correlation signatures of anti-GPCR antibodies changed dramatically in the patients with pulmonary involvement. Conclusions: This study demonstrates an association between pSS and autoantibodies recognizing GPCR, especially those functionally involved in immune cell migration and exocrine glandular secretion.